Uniting America : restoring the vital center to American democracy - Garfinkle, Norton, 1931-; Yankelovich, Daniel (Yale University Press, 2005)
In Uniting America, some of America's most prominent social thinkers - among them Francis Fukuyama, Daniel Yankelovich, Amital Etzioni, Alan Wolfe, Uwe Reinhardt and Thomas E. Mann - reject the myth of polarisation. On topics ranging from the war on terrorism, health care, economic policy and Social Security, to religion, diversity and immigration, the authors argue that there are sensible, centrist solutions that are more in keeping with prevailing public sentiment and that would better serve the national interest. On issue after issue, the authors show how the conventional framing of the debate in Washington has misled Americans, creating a series of false dilemmas and forcing choices between two extremes - at the expense of more balanced and pragmatic policy solutions based on enduring American values. Uniting America provides a blueprint for a fresh approach to American politics, grounded in moderation, pragmatism and the shared values that unite Americans.